2015
DOI: 10.1007/s11357-015-9808-7
|View full text |Cite
|
Sign up to set email alerts
|

Aging and low-grade inflammation reduce renal function in middle-aged and older adults in Japan and the USA

Abstract: The objective of this study was to investigate the effects of low-grade inflammation on age-related changes in glomerular filtration rate (GFR) in middleaged and older white Americans, African-Americans, and Japanese adults. Serum creatinine, C-reactive protein (CRP), and interleukin-6 (IL-6) levels were determined for 1570 adult participants in two surveys of aging in the USA and Japan (N = 1188 and 382, respectively). Kidney function declined with age in both countries and was associated with IL-6 and CRP. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
1
36
1
Order By: Relevance
“…Inflammation is increased within the aging kidney in humans, with proinflammatory cytokines detectable in the serum correlating with age-related renal disease. 155,156…”
Section: Inflammationmentioning
confidence: 99%
“…Inflammation is increased within the aging kidney in humans, with proinflammatory cytokines detectable in the serum correlating with age-related renal disease. 155,156…”
Section: Inflammationmentioning
confidence: 99%
“…In the current literature, the common ageing‐related diseases and conditions associated with increased CRP levels include CVD, hypertension, diabetes mellitus, chronic kidney injury, Alzheimer's disease and Parkinson's disease …”
Section: Crp and Ageing‐related Diseasementioning
confidence: 99%
“…Ethnic determinants may account for differences in CRP levels and their change over time, as studies have shown that younger African Americans have a steeper age‐related decline in eGFR, which is associated with increasing CRP, compared with non‐African Americans. Whereas Japanese elderly, for example, began to have steep changes in eGFR and indications of increased inflammatory activity after age 70 years …”
Section: Crp and Ageing‐related Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is increased within the aging kidney in humans, with pro inflammatory cytokines detectable in the serum correlating with age-related renal disease [35,36] . The increase of IL-6 may contribute, along with other proinflammatory factors, to the onset of many of the chronic age related diseases [37] , and may also be associated with mortality [38] .…”
Section: Discussionmentioning
confidence: 99%